Gender differences in hypertrophy, insulin resistance and ischemic injury in the aging type 2 diabetic rat heart. - Desrois, M; Sidell, R; Gauguier, D; Davey, C; Radda, G; Clarke, K (2004)
Aging and diabetes in women increase their susceptibility to myocardial ischemic injury, but the cellular mechanisms involved are not understood. Consequently, we studied the influence of gender on cardiac insulin resistance and ischemic injury in the aging of Goto-Kakizaki (GK) rat, a model of type 2 diabetes. Male and female GK rats had heart/body weight ratios 29% (P < 0.0001) and 53% (P < 0.0001) higher, respectively, than their sex-matched controls, with the female GK rat hearts significantly more hypertrophied than the male (P < 0.001). Glucose transporter (GLUT) 1 protein levels were the same in all hearts, but GLUT4 protein levels were 28% lower (P < 0.01) in all GK rat hearts compared with their sex-matched controls. In isolated, perfused hearts, insulin-stimulated (3)H-glucose uptake rates were decreased by 23% (P < 0.05) and 40% (P < 0.05) in male and female GK rat hearts, respectively, compared with their controls, with the female significantly more insulin resistant than the male GK rat hearts (P < 0.05). Protein kinase B protein levels and insulin-stimulated phosphorylation were the same in all hearts. During low-flow ischemia, glucose uptake was 59% lower (P < 0.001) in female, but the same as controls in male, GK rat hearts. Consequently, recovery of contractile function during reperfusion was 30% lower (P < 0.05) in female, but the same as controls in male GK rat hearts. We conclude that the aging female type 2 diabetic rat heart has increased insulin resistance and greater susceptibility to ischemic injury, than non-diabetic or male type 2 diabetic rat hearts.